Utilization of Teaching Materials to Improve Critical Thinking Skills in Anatomy and Physiology of the Human Body Learning for Biology Students - Kencanawati*, Indah; Siregar, Anggi Desviana (Jurnal IPA & Pembelajaran IPA, 2024)
The utilization of teaching materials plays a vital role in achieving educational objectives, especially in fostering CTS crucial for students to meet global challenges and solve complex problems. This study focuses on 5th-semester biology students enrolled in the Anatomy and Physiology of the Human Body (ANFISMAN) course. A quantitative approach is employed, utilizing a quasi-experimental Pretest-Post test control group design. Critical thinking levels are measured through structured essay assessments, comprising ten questions aligned with five critical thinking indicators: focus, reasoning, organization, prevalence, and integration. In the first phase, students understanding of the concepts is gauged, targeting comprehension in the context of critical thinking evaluation. The second phase assesses their ability to provide logical reasons for problem-solving, supported by factual evidence. The third phase examines students' skills in synthesizing conclusions, while the fourth phase evaluates their adherence to standard grammatical conventions. Finally, the fifth phase assesses the accuracy and clarity of responses, ensuring comprehensive evaluation based on evidence. The study sampled 48 students and revealed that teaching materials significantly enhanced CTS development, as demonstrated by a t-test significance value of 0.000, which is markedly below the 0.05 threshold. This indicates a notable difference in critical thinking outcomes between students using modified inquiry-based teaching materials and those who did not. Furthermore, the experimental group achieved a higher average N-Gain value of 0.4133 compared to the control group's 0.3828. These results highlight the effectiveness of well-structured teaching materials in fostering critical thinking within the ANFISMAN course, emphasizing in advancing biology education.